Late deterioration after decompression illness affecting the spinal cord. Issue 4 (December 1996) - Dyer, J; Millac, P
Abstract : A former amateur diver presented with a progressive paraparesis. Thirteen years previously he had developed acute spinal cord dysfunction immediately after dry hyperbaric exposure. He had completely recovered motor function in the intervening period. No alternative reason for the later decline emerged from detailed investigation.